Comparison of the development of the communicative competence of the blind and visually impaired in institutions and including schooling - Mateja Forte (University of Maribor Press, 2015)
The article is a research, belonging to the domain of practical/usable linguistics. The basis of the presented content is the communicative competence and the issue of its development by blind and visually impaired children. The methodology, used in the research, consists of primary and secondary materials. The secondary ones are theoretical, from: linguistics, psychology, medicine, pedagogies and special pedagogies. The primary materials can be divided in two sections. The first one is a comparison of two educational models for blind and visually impaired children, one from mainstream schools and the other from specialized institutions. The second part consists of four structured interviews, the analysis of which gives us the answer about the difference in the development of the communicative competence of the blind and the visually impaired in consideration of the chosen model of schooling.